Perlakuan Akuntansi Pembiayaan Ijarah dalam Rahn Berdasarkan PSAK No. 107 di PT. Pegadaian Syariah Cabang Hasanuddin - yusuf, mutmainna; Muchran, Muchran (Jurnal Ar-Ribh, 2018)
This study aims to determine the accounting treatment and financing of ijarah at PT Pegadaian Syariah Hasanuddin Branch. Analyzing the suitability of ijarah accounting treatment with PSAK 107. Analyzing ijarah financing with conformity to the National Sharia Council Fatwa No: 25 / DSN-MUI / III / 2002. The method used in the research is qualitative descriptive method. By conducting interviews with PT. The Hasanuddin Branch Pawnshop or by taking written data is then analyzed and compared between the real conditions that occur in the field into writing with the conformity of PSAK 107 and the fatwa of the national sharia council. The results of this study reveal that accounting treatment related to the recognition and measurement carried out by PT. Sharia Pegadaian Hasanuddin Branch is in accordance with PSAK 107, but related to the presentation and disclosure of PT. Sharia Pegadaian Hasanuddin Branch does not present and disclose financial statements specifically. Then the cost of ijarah (Mu'nah Pemamanan) applied by PT. Sharia Pawnshop Hasanuddin Branch is not in accordance with the National Sharia Council Fatwa No: 25 / DSN-MUI / III / 2002 where the amount of ijarah fees is not determined by the size of the loan. This is due to PT. The Hasanuddin Branch Pawnshop Unit in determining ijarah fees is based on the classification of marhun bih.